Sedimentation of a Fine Aerosol in the Acoustic Field and with the Electrostatic Charge of Particles - STEPKINA, Maria Yurievna; KUDRYASHOVA, Olga Borisovna; ANTONNIKOVA, Alexandra Alexandrovna (Archives of Acoustics, 2018)
Finding an efficient way to eliminate fine dust (particle diameter of 1–15 μm) from a room can be a challenging problem. Acoustic radiation emitters are widely used to accelerate particle coagulation and sedimentation. In this study, we propose one more method for depositing harmful particles – dispersion of electrostatically charged particles. These particles attract uncharged particles from the air and accelerate coagulation. The paper is devoted to a comparison of methods for the acoustic and electrostatic sedimentation of aerosols. The mathematical model for the coagulation of aerosols on the basis of Smoluchowski’s equation is proposed in the options corresponding to acoustic and electrostatic coagulation. A number of conclusions about the most effective conditions of sedimentation were made on the basis of the analysis of a kernel type of Smoluchowski’s integral equation. The results of the experiments on acoustic and electrostatic sedimentation of the model aerosol media (coal dust) are given. The results of the calculations according to the mathematical model of coagulation taking into account the proposed mechanisms for the sedimentation of aerosols in the acoustic field and electrostatic charging of particles are given.